2015
DOI: 10.1039/c5cp03798k
|View full text |Cite
|
Sign up to set email alerts
|

Cluster-continuum quasichemical theory calculation of the lithium ion solvation in water, acetonitrile and dimethyl sulfoxide: an absolute single-ion solvation free energy scale

Abstract: Absolute single-ion solvation free energy is a very useful property for understanding solution phase chemistry. The real solvation free energy of an ion depends on its interaction with the solvent molecules and on the net potential inside the solute cavity. The tetraphenyl arsonium-tetraphenyl borate (TATB) assumption as well as the cluster-continuum quasichemical theory (CC-QCT) approach for Li(+) solvation allows access to a solvation scale excluding the net potential. We have determined this free energy sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
74
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(77 citation statements)
references
References 97 publications
(126 reference statements)
3
74
0
Order By: Relevance
“…The Li + cation is mainly solvated by DMSO molecules at different concentration ratios of DMSO and ACN that is in qualitative agreement with the experiment . Cluster‐Continuum Quasichemical Theory calculations confirmed that the solvation free energy of Li + in DMSO is much more negative than in ACN and H 2 O . It was also shown that the solvation energy of Li + trended with solvent DN, and varied greater than that of O 2 − ions, which correlated with acceptor number .…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…The Li + cation is mainly solvated by DMSO molecules at different concentration ratios of DMSO and ACN that is in qualitative agreement with the experiment . Cluster‐Continuum Quasichemical Theory calculations confirmed that the solvation free energy of Li + in DMSO is much more negative than in ACN and H 2 O . It was also shown that the solvation energy of Li + trended with solvent DN, and varied greater than that of O 2 − ions, which correlated with acceptor number .…”
Section: Introductionsupporting
confidence: 80%
“…[23] Cluster-Continuum Quasichemical Theory calculations confirmed that the solvation free energy of Li + in DMSO is much more negative than in ACN and H 2 O. [24] It was also shown that the solvation energy of Li + trended with solvent DN, and varied greater than that of O 2 À ions, which correlated with acceptor number. [25] Furthermore, a significant inhibition of the Li + and Cl À ionassociation reaction in pure DMSO was shown compared to the ion-aggregation in ACN.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the cluster‐continuum quasichemical approach was used to establish a theoretical single‐ion bulk solvation free energy scale in water, methanol, DMSO, and acetonitrile solvents . The lithium ion was used as reference to establish the scale, because in this case the assumptions of the cluster‐continuum method are accurate.…”
Section: Theorymentioning
confidence: 99%
“…In fact, ions in solution are much more difficult to describe and the problem of net potential felt by the ion generates different solvation free energy scales. 21,[36][37][38] However, even more important than predicting absolute solvation free energy values is to predict correct variation of the solvation free energy between transition states and reactants as well as between products and reactants. This ability would lead to reliable prediction of solvent effects on chemical reactions.…”
Section: Introductionmentioning
confidence: 99%
“…20 Methanol is a polar protic solvent and its ability to solvate ions is similar to water. 21,22 In addition, it has the advantage of solubilize many organic molecules not soluble in water. Some usual dipolar aprotic solvents are dimethyl sulfoxide (DMSO), dimethylformamide (DMF) and acetonitrile.…”
Section: Introductionmentioning
confidence: 99%